Association between some Drought Indices and Socio-productive Impacts in the Northern Pacific Region of Costa Rica - Quesada-Hernández, Luis Eduardo (2020)
[Introduction]: The droughts in Costa Rica are an extreme hydrometeorological event that affects many crops producers and society in general. [Objective]: To define which drought index shows the strongest relationship with drought impacts reports in social and productive sectors for three areas in Guanacaste, province of Costa Rica located within the Central American Dry Corridor (CSC). [Methodology]: A drought impact dataset for the period 1970-1999 was created from different sources of information: Desinventar database, EM-DAT, information from the National Meteorological Institute of Costa Rica and different press reports. This database is compared to the following six drought indexes using the logistic regression technique: the Standardized Precipitation Index at scales of 6 and 12 months (SPI 6 and SPI 12 respectively), the Drought Severity Index and the Hydrological Index of Palmer (PDSI and PHDI respectively), the Drought Recognition Index (RDI), and the Modified Rainfall Anomaly Index (mRAI). [Results]: In general, the most appropriate index to link drought and social and productive impact reports is the SPI for 6 and 12 months. [Conclusions]: In all the areas of study, this index has a high (low) probability of many (zero) impacts when it is in moderately and severely dry (wet) conditions.